2009
DOI: 10.1074/jbc.m809173200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of β-PrP

Abstract: Prion propagation involves a conformational transition of the cellular form of prion protein (PrP C ) to a disease-specific isomer (PrP Sc ), shifting from a predominantly ␣-helical conformation to one dominated by ␤-sheet structure. This conformational transition is of critical importance in understanding the molecular basis for prion disease. Here, we elucidate the conformational properties of a disulfide-reduced fragment of human PrP spanning residues 91-231 under acidic conditions, using a combination of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 82 publications
(119 reference statements)
6
42
0
Order By: Relevance
“…The deconvoluted peak (see insets) derived from each sample corresponded to the predicted molecular mass of oxidized SHaPrP(90-231), 16,240 Da. This is considered to be more biologically relevant than its reduced counterpart [3,43]. This is because the oxidized construct is structured due to the presence of a disulphide bond.…”
Section: Resultsmentioning
confidence: 97%
“…The deconvoluted peak (see insets) derived from each sample corresponded to the predicted molecular mass of oxidized SHaPrP(90-231), 16,240 Da. This is considered to be more biologically relevant than its reduced counterpart [3,43]. This is because the oxidized construct is structured due to the presence of a disulphide bond.…”
Section: Resultsmentioning
confidence: 97%
“…Significant amounts of b-structure have been detected in oligomers of prion protein (PrP) [90,91]. PrP oligomers formed at low pH were b-sheet rich and had lower stability and lower extent of b-structure compared to fibrils [90,92,93]. These oligomers were not on the pathway for fibril formation.…”
Section: Other Proteinsmentioning
confidence: 99%
“…Previous studies had suggested the protein formed a molten globule at low pH (55)(56)(57)(58). Surprisingly, at pH 4.4, the Trp triplet decays remain single-exponential even at 0 M GdnHCl, suggesting the protein is freely diffusing and there is no stable structure.…”
Section: Resultsmentioning
confidence: 88%